Associations Between Reported Dietary Sodium Intake and Osteoporosis in Korean Postmenopausal Women: The 2008-2011 Korea National Health and Nutrition Examination Survey. (July 2017) - Kim, Yunmi; Kim, Hyun-Young; Kim, Jung Hwan
Osteoporosis is prevalent among postmenopausal women, and increasing evidence has linked salt intake with this disease. In this article, we explored the association between dietary sodium intake and osteoporosis in Korean postmenopausal women. We analyzed data for 3635 postmenopausal women extracted from the 2008-2011 Korea National Health and Nutrition Examination Survey. We found that 1542 participants (42.4%) have osteoporosis. The adjusted prevalence rates of osteoporosis at the lumbar spine were significantly higher in participants who consumed ≥4001 mg of salt than those who consumed ≤2000 mg. At the femoral neck, rates were significantly higher for those who consumed ≥5001 mg compared with those who consumed ≤4000 mg. Participants with a higher sodium intake showed a significantly higher odds ratio of developing lumbar and femoral neck osteoporosis, compared with those with a lower intake. Our results suggest that excessive daily sodium intake is associated with a higher osteoporosis prevalence in Korean postmenopausal women.